Usefulness and practicality of a multidisease screening programme targeting migrant patients in primary care in Spain: a qualitative study of general practitioners. Issue 11 (16th November 2022) - Gonçalves, Alessandra Queiroga; Sequeira-Aymar, Ethel; Aguilar Martín, Carina; Dalmau, Rosa Maria; Cruz, Angeline; Evangelidou, Stella; Hargreaves, Sally; Requena-Mendez, Ana; Jacques-Aviñó, Constanza
Abstract : Objectives: Some migrant groups are disproportionately affected by key infectious diseases in European countries. These pose a challenge for healthcare systems providing care to these groups. We aimed to explore the views of general practitioners (GPs) on the acceptability, adaptability and feasibility of a multidisease screening programme based on an innovative clinical decision-support system for migrants (the ISMiHealth tool), by examining the current gaps in healthcare provision and areas of good practice and the usefulness and limitations of training in the health needs of migrants. Methods: We undertook a qualitative descriptive study and carried out a series of focus groups (FGs) taking a pragmatic utilitarian approach. Participants were GPs from the four primary healthcare (PHC) centres in Catalonia, Spain, that piloted an intervention of the ISMiHealth tool. GPs were recruited using purposive and convenience sampling. FG discussions were transcribed and analysed using thematic content analysis. Results: A total of 29 GPs participated in four FGs. Key themes identified were: (1) GPs found the ISMiHealth tool to be very useful for helping to identify specific health problems in migrants, although there are several additional barriers to screening as part of PHC, (2) the importance of considering cultural perspectives when caring for migrants, and of the impact of migration on mental health, (3) the important role of PHC in healthcare provision for migrants and (4) key proposals to improve screening of migrant populations. GPs also highlighted the urgent need, to shift to a more holistic and adequately resourced approach to healthcare in PHC. Conclusions: GPs supported a multidisease screening programme for migrant populations using the ISMiHealth tool, which aided clinical decision-making. However, intercultural participatory approaches will need to be adopted to address linguistic and cultural barriers to healthcare access that exist in migrant communities.